Why Consumers Choose Counterfeits: An Integrated Model of Psychological and Social Determinants - Mardiatmi, Bernadin Dwi; Wikantari, Maria Assumpta; Pusporini, Pusporini; Argo, Jenji Gunaedi; Khoerunisa, Mutia (Yayasan Gema Bina Nusantara, 2025)
Counterfeit consumption has become a global issue that undermines intellectual property rights, damages brand equity, and influences consumer behavior across markets. This study aims to analyze the behavioral characteristics influencing consumers’ purchase decisions for counterfeit products, particularly within the Indonesian context. Using the Theory of Planned Behavior (TPB), Self-Determination Theory (SDT), Neutralization Theory, and Perceived Value Theory as analytical frameworks, the research investigates how attitudes, social influence, novelty seeking, status consumption, brand consciousness, perceived risk, and personal integrity shape purchase intentions. A quantitative survey of 240 Indonesian consumers who have purchased or been exposed to counterfeit products was conducted, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The findings reveal that attitude, social influence, novelty seeking, and brand consciousness have significant positive effects on counterfeit purchase intention, while perceived risk and integrity exhibit weaker or negative effects. Awareness mediates these relationships, reducing purchase likelihood when ethical and legal knowledge is high. The study contributes theoretically by extending TPB with psychological and social-value constructions and offers managerial implications for policy, education, and anti-counterfeiting strategies.